تصميم الأذرع الالية و استخدامها في عمليات الانتاج : بالتطبيق في الشركة العامة للسمنت الشمالية - صباح أنور يعقوب (PROSPECTIVE RESEARCHES, 2023)
t The current paper aims to design and study the robot and its controls using a computer and a C++ program. The interface we used between the computer and our designed robot was the parallel port. The idea was to produce a robotic arm that can be controlled to move objects (Cement Container) between production lines within cement factory in the north cement company. Two models were designed and tested in the study. The first was built of steel and was capable of lifting relatively higher weights but it was rather slower than the second model that was built of aluminum alloy. Finally both models were capable of free movement in all directions.